2004
DOI: 10.1124/mol.104.001354
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mechanisms of Nitric Oxide- and Peroxynitrite-Induced Cell Death

Abstract: Nitric oxide (NO) contributes to cellular degeneration in various disorders, particularly in the nervous system. NO targets cell proteins such as soluble guanylyl cyclase, but its detrimental effects are generally attributed to its reaction product with superoxide, peroxynitrite. To understand the mechanisms of NO-induced cell stress, we studied the effects of the NO donors diethylenetriamine and spermine NONOate and the peroxynitrite donor 5-amino-3-(4-morpholinyl)-1,2,3-oxadiazolium chloride (SIN-1) in SH-SY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…This observation further authenticate that what we measured with H 2 DCF-DA was peroxynitrite anions but not other oxidant species (35,36). Previous studies from our laboratory have suggested that NO and peroxynitrite ions are toxic to dopaminergic neurons (37,38). Furthermore, LPS also is known to activate protein kinase C, protein-tyrosine kinases, MAP kinases and NF-kB all have been implicated in the release of several cytotoxic factors such as NO and various cytokines (39)(40)(41)(42).…”
Section: Discussionsupporting
confidence: 88%
“…This observation further authenticate that what we measured with H 2 DCF-DA was peroxynitrite anions but not other oxidant species (35,36). Previous studies from our laboratory have suggested that NO and peroxynitrite ions are toxic to dopaminergic neurons (37,38). Furthermore, LPS also is known to activate protein kinase C, protein-tyrosine kinases, MAP kinases and NF-kB all have been implicated in the release of several cytotoxic factors such as NO and various cytokines (39)(40)(41)(42).…”
Section: Discussionsupporting
confidence: 88%
“…In the Fenton reaction, reduction of H 2 O 2 by iron results in the production of the highly reactive and toxic hydroxyl radical [32]. SIN-1 generates NO and superoxide in equimolar amounts, thereby producing [33]; moreover, NO is thought to be a potent toxin independent of peroxynitrite formation [34]. Both isorhamnetin and luteolin inhibited neuronal cell damage induced by H 2 O 2 or SIN-1; in these experiments, isorhamnetin was weaker in ROS scavenging activity but better at inhibiting NO formation than luteolin (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive, unregulated NO production can also lead to the formation of reactive nitrogen species that can oxidize lipids, damage DNA, and cause protein modifications of important cellular proteins and enzymes [27]. The ability of NO or reactive nitrogen species to alter mitochondrial function and damage proteins may result in NO-mediated apoptosis or necrosis depending on the amount of NO and reactive nitrogen species generated [28].…”
Section: Discussionmentioning
confidence: 99%